Mechanism of removal and degradation characteristics of dicamba by biochar prepared from Fe-modified sludge. (1st December 2021) - Wan, Chunli; Li, Huiqi; Zhao, Lianfa; Li, Zhengwen; Zhang, Chen; Tan, Xuejun; Liu, Xiang
Abstract: The pyrolysis of excess sludge derived from wastewater treatment plants to prepare biochar can achieve the mass-reduction and harmlessness of solid waste, but it is also necessary to further explore the application prospect of these biochars as a resource for wastewater treatment. In this study, Fe-modified biochar (BC–Fe) was prepared by pyrolysis of excess sludge modified by FeCl3 solution. The molecular structure, elemental valence state, and composition of biochars were comprehensively investigated. The results showed that, compared with the biochar prepared from sludge without modification (BC-blank), the O/C ratio of BC-Fe increased from 0.07 to 0.12, and the (N + O)/C ratio increased from 0.21 to 0.27, indicating increased polarity and weakened aromaticity. The ratio of integrated intensity of the D band and G band in the Raman spectrum increased from 1.34 to 2.40, showing the increased defect structure of the biochar obtained by Fe modification. In the reaction between BC-Fe and dicamba, the removal rate of dicamba reached 92.1% within 180 min, which was far higher than the 17.8% of BC-blank. It was confirmed the adsorption removal dominated and accounted for 70.6% of the dicamba removal by BC-Fe, and the adsorption capacity of biochar could be significantly enhanced by Fe-modification by 5.3 times. Moreover, the persistent free radicals (PFRs) on the surface of biochar was detected by an electron paramagnetic resonance analyzer, and the decline of PFRs signals after the reaction revealed that PFRs participated in the degradation process of dicamba. Through Q-TOF analysis, it could be concluded that dicamba was first converted to 3, 6-dichlorosalicylic acid (DCSA) by PFRs reduction and then further transformed to 3, 6-dichlorogentisic acid (DCGA). This study provided a reference for the understanding of the removal mechanism of dicamba by Fe-modified biochar and offered an application potential of biochar derived from Fe-containing sludge for the pollution control of dicamba pesticide pollutants. Graphical abstract: Image 1 Highlights: Fe-modified biochar possessed increased defect structure and weakened aromaticity. By Fe-modified biochar, the removal rate of dicamba was 92.1% within 180 min. Fe modification increased the adsorption capacity of sludge biochar by 5.3 times. PFRs reduction of BC-Fe was directly involved in the degradation of dicamba.